PENGARUH PENGUNGKAPAN INFORMASI MODAL INTELEKTUAL DALAM LAPORAN TAHUNAN TERHADAP KAPITALISASI PASAR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2013 - Alfianti Permatasari; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of disclosure of intellectual capital in the annual report manufacture companies listed on the Stock Exchange for the period 2010-2013 to company's market capitalization. This study refers on research of Anam et al (2011) and Rachmi (2014) by modifying the sample and the addition of variables level of intellectual capital and ownership concentration variables as control variables. This research is written because there is a asymetry information between companies and stakeholders about intellectual capital which is expected to affect market capitalization.This study uses secondary data derived from the annual report of manufacture companies listed on the Indonesian Stock Exchange (BEI) in the period 2010 to 2013. The sample of this study was interpreted by a purposive sampling method. The total sample in this company is 160 manufacturing company. The analysis method used in this research is multiple linear regression analysis.The  results  of  this  study found that  the  level  of  disclosure  of  intellectual  capital in manufacture companies listed on the Stock Exchange in 2010-2013 significant positive effect on the market capitalization. This results gives the conclusion that the disclosure of intellectual capital will reduce asymmetry information and will provide a positive signal of comapny, so give influence to market capitalization. However, there is a control variables in the study that is leverage have not significant effect on the market capitalization.